Comparative Analysis of Proteins Involved in Energy Metabolism and Protein Processing in Pyropia haitanensis at Different Salinity Levels - Wen, Jian; Wang, Wenlei; Xu, Kai; Ji, Dehua; Xu, Yan; Chen, Changsheng; Xie, Chaotian (Frontiers in Marine Science, 2020)
The worsening of soil salinization has become an important factor limiting crop yield and quality. Pyropia haitanensis grows in the intertidal zone and is highly salt tolerant. The response mechanism of organisms exposed to stress is linked to energy metabolism and protein processing. However, the effect of hypersaline stress on the energy metabolism and protein synthesis of the P. haitanensis thallus has not been reported. Therefore, the objective of this study was to apply data-independent acquisition (DIA) technology to analyze the differences in the changes to the abundance of proteins related to energy metabolism and protein processing in P. haitanensis thalli exposed to salinity stress (100‰) and semilethal salinity (110‰). The examination of energy metabolism in algae under hypersaline stress revealed the decreased abundance of phosphofructokinase inhibits the glycolytic pathway. However, increases in triosephosphate isomerase levels and the enhancement of the pentose phosphate pathway minimize this inhibitory effect, while also providing substrates for the citric acid cycle as well as energy for physiological and biochemical algal reactions under hypersaline stress conditions. Regarding the protein processing related to the endoplasmic reticulum, increases in the abundance of CNX, the transporter COP II, heat shock proteins, protein disulfide isomerase, and other proteins related to endoplasmic reticulum quality control will ensure proteins are synthesized in algae under hypersaline stress. Increases in the levels of endoplasmic reticulum-associated degradation recognition protein BiP and transporter Sec61 as well as the ubiquitination degradation system-related proteins will maintain the dynamic balance between protein folding and clearance in algae. Moreover, algae are tolerant to 100‰ salinity, but 110‰ salinity is semilethal to algae. The abundances of citrate synthase, 6-phosphoglucose dehydrogenase, protein disulfide isomerase, and other related proteins increased under 100‰ salinity stress, but not under 110‰ salinity stress. Accordingly, in response to 100‰ salinity stress, P. haitanensis thalli may induce metabolic activities to satisfy the requirements of physiological and biochemical reactions. Furthermore, protein processing and synthesis may be stabilized to ensure necessary stress reactions are completed. The results of this study provide data potentially useful for investigating plant stress resistance mechanisms and for cultivating new salt-tolerant varieties.